Impact Of The Russian-Ukraine Invasion On Wheat Imports In Indonesia Implications On Economic Growth In Indonesia - Noor, Muhamad Arief; Pardian, Ramadani; Lesmana, Asep Surya; Nurhakim, Rahman (Jurnal Mamangan, 2023)
This research aims to determine the Impact Of The Russian-Ukraine Invasion On Wheat Imports In Indonesia. Implications For Economic Growth In Indonesia. The data in this study is secondary data in the form of time series data during the period 2010 – 2020. Based on the results of the research and analysis of the discussion, the researchers concluded several things as follows; Wheat consumption variable, rupiah exchange rate and wheat price simultaneously have a significant effect on foreign exchange reserves. With the impact of some of the variables above, Indonesia's wheat imports have increased so that full employment opportunities will be achieved and unemployment will decrease. The variable of wheat consumption partially has a significant and positive effect on imports of Indonesian wheat. The high value of wheat consumption will increase imports of Indonesian wheat in the country so that the need for flour in Indonesia is met. The exchange rate variable partially has a positive and significant and negative effect on Indonesian wheat imports. The international wheat price variable partially has a positive and significant effect on Indonesian wheat imports. Indonesian wheat import variable partially has a significant and positive effect on economic growth. The increase in Indonesian wheat imports indicates that economic growth will increase.The equation obtained shows an increasing trend. The following are the results of the projected volume of wheat imports in Indonesia in 2018-2032 using the linear trend equation. Consumption of wheat flour, imports of corn, exchange rates and international wheat prices have a significant effect on the volume of imports of wheat in Indonesia